Pengaruh Perputaran Modal Kerja dan Perputaran Piutang Terhadap Return on Equity pada Perusahaan Sektor Properti dan Real Estate Periode 2019-2023 - Chintia Listanti Kamaru; Hais Dama; Selvi (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to examine the effect of working capital turnover and accounts receivable turnover on Return on Equity (ROE) in property and real estate subsector companies during the 2019-2023 period. The data collection technique in this research is secondary data, specifically financial reports published by property and real estate companies listed on the Indonesia Stock Exchange (IDX). The sample selection technique employed purposive sampling, resulting in a total sample of 14 companies. The data are analyzed using multiple linear regression analysis. The result of hypothesis using multiple linear regression analysis indicate that working capital turnover does not have a partial effect on return on equity, whereas accounts receivable turnover has a partial effect on return on equity. However, when analyzed simultaneously both working capital turnover and accounts receivable turnover influence return on equity.